Fraud Diamond Theory Detect Financial Statement Fraud in Manufac-turing Companies on The Indonesia Stock Exchange - Fitriana Fitriana; Didin Saepudin; Rachmat Agus Santoso (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
Financial statement fraud is fraud committed by management in the form of material misstatements of financial statements, one theory to detect it is the fraud diamond theory. This research aims to determine the effect of the fraud diamond theory in detecting financial statement fraud. The proxies fraud diamond used in this study are financial stability, nature of industry, change in auditor and change of director. This research method is descriptive and verification with panel data regression analysis processed using the Eviews 9 application, a secondary data source on fabricating organizations recorded on the Indonesia Stock Trade in 2015 – 2019, with a population of191 companies using purposive sampling technique. The number of samples is 119 companies. Condition Financial stability, nature of industry, change in auditor, change of director and financial statement fraud in The manufacturing company that is the sample is in good condition, because there is no indication of committing financial statement fraud. Simultaneous test results of all independent variables have a significant effect on the direction of a positive relationship to financial statement fraud. The test results partially and partially financial stability and nature of industry have a significant effect on the direction of the negative relationship to financial statement fraud, then change in auditor and change of director have no effect on the direction of the negative and positive relationship on financial fraudulent statements.